Molecular characterization of Listeria monocytogenes strains isolated from Hospital Materno Infantil San Bartolomé, Lima-Perú - Villegas, Miguel (2012)
Listeriosis primarily affects pregnant women, newborns, elderly people and patients with low immune response, among others, and is caused by Listeria monocytoges. In this study we characterized molecularly 20 strains of L. monocytogenes isolated from 18 cases of perinatal listeriosis in Hospital San Bartolomé of Lima-Perú, during 2001 to 2005 years. The bacteria were characterized initially by conventional bacteriological testing, such as β-hemolysis incomplete, CAMP reaction positive with Staphylococcus aureus and negative with Rhodococcus equi and the differential utilization of carbohydrates as D-glucose and L-rhamnose, but not D-xylose and D-mannitol. Then, strains were identified by polymerase chain reaction (PCR) and typified by the technique of Random Amplified Polymorphic DNA (RAPD) primers using OMP-01, M13, M132, PJ108 and PJ108. With primers OMP-01 and PJ108 were obtained six RAPD patterns: eight strains with AI pattern, three with AII, AIII and BII patterns each one, two and one with BI and AIV patterns, respectively. In conclusion, from the 18 cases of listeriosis were isolated 20 strains of L. monocytogenes with six different genotypes being the AI RAPD pattern the most common with 40% (8/20) of the strains studied.